The Resource Based View and Competitive positioning: Impotance of Market Based Resources. - Agarwal, Namrata (2006)
The dissertation examines the importance of market based resources in achieving competitive positioning strategies. The two contradictory paradigms, resource based view and marketing perspective have been explored in depth. The subject of my research in this context has been the Indian market. The economy of India in a robust demonstration of its nascent strength has been growing at 8.5 and 7.5 percent in the two previous years and is projected to grow at 8.1 percent in the current year. With globalization and liberalization there has been an effective increase in competition. Indian companies are increasingly moving from being self-sufficient to high profit making firms and are recognized as being internationally competitive. Not only are the domestic firms are improving and expanding their operations but also the multinationals and big organizations all throughout the world are increasingly viewing India as an attractive business destination. With the help of qualitative methodology the various factors affecting the competitive positioning have been studied in the light of resource based view. Therefore the research gives a comprehensive picture of important factors considered in competitive scenario. Based on the study, recommendations for future research have been stated.